Effect of Lifestyle Counseling for Women with Gestational Diabetes on Fetal and Maternal Outcomes at Assiut University - Nagah F. Mohamed; Mervat A. Mahmoud; Ghadah Abdelraham; Tarek Abd Elrady; Amany Aly Ahmed (International Journal of Women's Health Nursing And Practices, 2023)
Gestational diabetes mellitus is a serious and often ignored risk to the health of mothers and children. Aim of the Study: To assess the effect of lifestyle counseling among women with gestational diabetes on fetal and maternal outcomes at Assiut University. Materials and Method: Antenatal care clinics hosted a pre-test and post-test for a quasi-experimental study. Sample: A total of 365 women in total attended antenatal care clinics. Setting of Study: The study was carried out at the Woman's Health Hospital at Assiut University and the antenatal care clinics in Assiut City, which serve the western area. Tools: Two instruments: a follow-up sheet and a structured interviewing questionnaire. Results: Blood sugar measurement and workout practice differed statistically significantly (P value = 0.000). Conclusion: The outcomes for mother and fetus with gestational diabetes were improved by lifestyle counseling. Recommendations: Women who are at risk of gestational diabetes mellitus should receive public education through the media to help prevent or lessen the difficulties that come with it for both mothers and newborns.
Keywords: fetus; gestational diabetes mellitus (GDM); lifestyle; pregnancy outcomes